A Note on Multiplicative Fuzzy on BP-Algebras - Abisha, V.; Kandaraj, N.; Thiruveni, V. (Communications in Mathematics and Applications, 2025)
Multiplicative fuzzy sets are defined by combining the membership values of the elements in a fuzzy set. This can be considered a generalization of fuzzy sets. Multiplicative fuzzy sets are useful in areas like quantum mechanics. In this paper, we define multiplicative fuzzy BP-algebras using the multiplication operation on membership functions and investigate some of their properties. Multiplicative fuzzy topological BP-algebras are also discussed.
Keywords: Absorbing subset; BP-Absorbing subset; Graded set; Multiplicative Fuzzy BP-Algebra